2016
DOI: 10.1900/rds.2016.13.158
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Existing Diabetic Foot Screening Guidelines

Abstract: ■ Abstract AIM:To evaluate critically the current guidelines for foot screening in patients with diabetes, and to examine their relevance in terms of advancement in clinical practice, improvement in technology, and change in socio-cultural structure. METHODS: A structured literature search was conducted in Pubmed/Medline, CINAHL, Cochrane Register of Controlled Trials, and Google between January 2011 and January 2015 using the keywords '(Diabetes) AND (Foot Screening) AND (Guidelines)'. RESULTS: Ten complete d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 61 publications
1
49
0
1
Order By: Relevance
“…ing the various screening criteria [20]. Foot pressure measuring is a case in point, with the potential to become a screening guideline since, at the moment, there is absolutely no reference to foot pressure assessment as a means of preventing foot ulceration [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ing the various screening criteria [20]. Foot pressure measuring is a case in point, with the potential to become a screening guideline since, at the moment, there is absolutely no reference to foot pressure assessment as a means of preventing foot ulceration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for diabetes involves the identification of asymptomatic individuals who are at high risk of developing the disease or its complications through appropriate screening tests [20]. Hence, the investigation of peak plantar pressure alterations in the non-symptomatic diabetic foot may be an important procedure for avoiding foot complications in high-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Stephens et al reported that the general practice for detecting PAD was mainly focused on pulse palpation, physical examination, history taking and patient reporting symptoms of intermittent claudication, the same methods of assessment for PAD which were used back in 1996 [11]. Although there is vast knowledge with regards to PAD, there seems to be lack of knowledge and consensus regarding the best method of assessment of PAD in patients living with diabetes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of guidelines and consensus documents have been released and regularly adjourned over the years, and study groups, and even scientific societies, have been created with DF as the subject of interest and focus for research [1][2][3] .…”
Section: Prefacementioning
confidence: 99%